Preparation and Study of Some Pyridinium Chloride Derivatives as Corrosion Inhibitors for Mild-Steel in 1M H2SO4 Aqueous Solution - Mahmood, Atheer Fadhel; Shihab, Mehdi Salih (Al-Nahrain Journal of Science, 2018)
Pyridinium chloride derivatives, namely: 1-benzyl-4-(2-cyclohexylidenehydrazinecarbonyl) pyridinium chloride, C1; 1-benzyl-4-(2-(1-phenylethylidene) hydrazinecarbonyl) pyridinium chloride, C2; 1-benzyl-4-(2-(diphenylmethylene)hydrazinecarbonyl) pyridinium chloride, C3, were prepared and studied as corrosion inhibitors for mild steel in 1M H2SO4 aqueous solution using weighting loss measurements for 24 hours at 30oC. The results showed that inhibition efficiency for all pyridinium chloride derivatives have rapprochement in value with the highest concentration. Increasing in inhibitor concentration accompanies with corrosion rate decreases, inhibition efficiencies increase and surface coverage degree increases. The free energy values of adsorption revealed physisorption effect for (C1, C2, and C3) and gave useful information to predict the interaction between the surface of metal and the organic molecules as corrosion inhibitors.